Supervised Learning from Data Mining on Process Data Loggers on Micro-Controllers - Saputra, Adi Dwifana Saputra; Hindarto, Djarot; Haryono, Haryono (Politeknik Ganesha Medan, 2023)
In processing data science, data is needed as input. Sometimes the data needed does not exist in public data, this is where the purpose of this research is made. The acquisition process is so important to process information into data. After that, the data is processed to make a decision. Micro-controller in controlling conditions, such as temperature, and humidity are very common devices, and a lot of research has been done. Sometimes discussing it only shows how to create a series and save it on online platforms, such as firebase, tinger.io, and many others online platforms. So that the process of storing data on an external or online platform is an advantage for platform providers, where platform providers do not need to do business and get data for free. This is without realizing the researchers who have produced a micro-controller device. Many platforms for storing data range from hardware and software devices. Some devices are paid or open source. This research uses software tools that are open source. Because using open source-based tools it will be easy to develop and for further research purposes. The development of the following research by entering code into a micro-controller system or what is called an embedded system. Data is a very valuable asset. Because data is one of the most important components in processing in data science. And it is better to take care of the data logger. This research uses Arduino as a micro-controller and ultrasonic distance sensor and potentiometer